Тарасова гора як рефлексивне середовище творчості Олександра Саєнка - Чулкова, Т.М. (Сіверщина в історії України, 2021)
У статті проведено аналіз творчості українського митця, майстра народного декоративного мистецтва Олександра Саєнка (1899–1985), уродженця Сіверщини, через призму його мистецьких рефлексій від відвідування Шевченківських місць та творчості Кобзаря. Досліджено мистецький доробок художника, який вирізнявся глибокою патріотичністю та національною самобутністю, що супроводжувалась збереженням і відтворенням українських мистецьких традицій, популяризацією українського стилю в образотворчому, декоративно-ужитковому мистецтві та архітектурі. Відзначено роль та місце творчості Тараса Шевченка, Тарасової гори – місця вічного спочинку видатного художника й поета – не лише у творчості, а й у житті Олександра Саєнка. Опрацьовано архівні джерела Шевченківського національного заповідника, на основі яких встановлено грані співпраці художника з музеєм Тараса Шевченка у Каневі та визначено його внесок у мистецьку скарбницю народної Святині. In the article was analyzed the work of Oleksandr Saienko a native of Sivershchyna the Ukrainian artist, the master of folk decorative art (1899– 1985), through the prism of his artistic reflections from visiting Shevchenko’s places, including the burial place of Taras Shevchenko in Kaniv, and Kobzar’s work. The multifaceted artistic work of the artist, which is characterized by deep patriotism and national identity, was explored. It is proved that the work of the famous Ukrainian was accompanied by preservation and reproduction of folk art traditions, popularization of Ukrainian style in fine, decorative and applied arts and architecture by rethinking the influence of folk traditions to the development of that time Ukrainian art, search for new artistic techniques. The role and place of Taras Shevchenko, his work, Tarasova Hora – the place of eternal rest of the outstanding artist and poet not only in his work, but also in the life of Oleksandr Saienko were identified. The influence of Tarasova Hora as a creative reflective environment on the artistic originality of Oleksandr Ferapontovych Saienko’s works and their perception by his contemporaries and representatives of future generations is outlined. The artist’s daughter memories, the art critic Nina Saienko were collected. A documentary and information resources of the sector of exposition and excursion work of the Shevchenko National Reserve research department were drafted. Archival sources and materials of the reserve’s stock collection were studied, on the basis of which the facets of the artist’s cooperation with the Shevchenko National Reserve in Kaniv were established and his contribution to the artistic treasury of the Ukrainian National Shrine was determined.